Survey of Low Earth Orbit Satellite Communication Network Routing Technology - Shuang ZHENG; Xing ZHANG; Wenbo WANG (天地一体化信息网络)
Low earth orbit satellite communication network is an important part of the internet of everything era, but the characteristics of satellite constellation topology such as high dynamic, limited heterogeneous resources and unbalanced network service capacity make the traditional routing protocol applied to the ground network no longer suitable for low earth orbit satellite network.In this regard, scholars at home and abroad had carried out extensive research on low-orbit satellite routing technology.Firstly, the research status of low-orbit satellite routing was discussed from inter-satellite routing and satellite-to-ground routing, and the inter-satellite routing technologies with business as the core and topology as the core were compared in detail.On this basis, the key problems faced by low-orbit satellite routing strategies were analyzed, namely, high dynamic network topology, large inter-satellite link propagation delay, uneven network load and limited on-board resources.The future research of routing technology was prospected accordingly.